PENERAPAN METODE PEMBELAJARAN ROLE PLAY TERHADAP PRESTASI BELAJAR DI SMP ISLAM TERPADU RUMBO KABUPATEN ENREKANG - Amri, Muhammad Ulil; Mustamin; Hasriani, Andi; Wahab, Abdul; Ahmad (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to improve students' learning achievement in the subject of Aqidah Akhlak through the application of the Role Play learning method in class VII of Rumbo Integrated Islamic Junior High School, Enrekang Regency. The research was motivated by the low learning achievement of students as indicated by only 9 out of 31 students (29.03%) who achieved the Minimum Completion Criteria (KKM) of 75, while 22 students (70.97%) had not achieved completion. This study used the Classroom Action Research (CAR) method with a constructivist approach which was implemented in two cycles. Each cycle includes four stages, namely planning, action implementation, observation, and reflection. The research subjects were 31 students of class VII of Rumbo Integrated Islamic Junior High School, Enrekang Regency, Academic Year 2025/2026. Data collection techniques used observation, interviews, tests, and documentation, while data analysis was carried out quantitatively and qualitatively. The results of the study showed that the application of the Role Play method was able to improve student activity and learning achievement. In the pre-cycle stage, the average score was 43.74 with a learning completion of 29.03%. After the actions in Cycle I, the average score increased to 75.67 with a learning completion of 70.97%. Furthermore, in Cycle II, the average score increased again to 82.90 with a learning completion of 87.10%, thus exceeding the research success indicator set at 80%. In addition to improving learning achievement, the Role Play method also increases student activity, cooperation, self-confidence, communication skills, and participation during the learning process. Thus, the Role Play learning method has proven effective in improving student learning achievement in the subject of Aqidah Akhlak, class VII of Rumbo Integrated Islamic Middle School, Enrekang Regency.